Students’ transition experiences in the seventh grades in a laboratory school - Abela, Rosario P.; Truya, Rizalina D.; Bellen, Joy A. (Intelektual Pustaka Media Utama, 2025)
The transition to high school often induces feelings of discomfort among students, potentially leading to stress and challenges, especially given their diverse socioeconomic backgrounds. If left unaddressed, these difficulties may contribute to disengagement, classroom challenges, and, in some cases, academic setbacks or dropping out. This study examines the transition experiences of grade seven students (n=144; 81 females and 63 males) enrolled in a laboratory school in Leyte. It focuses on their perceived appreciation of their former schools, the importance of acquired competencies, and the difficulties encountered during the transition. Findings indicate that respondents generally highly appreciate their former schools and recognize the value of the competencies they developed while reporting moderate difficulty levels in the transition. Students from public schools, in particular, showed a strong appreciation for their previous school environment and competencies. Additionally, students with higher grades expressed a greater appreciation for their former school and reported lower levels of difficulty in adjusting. The results suggest that enhancing school engagement and fostering a sense of belonging could ease the transition process, helping students better adapt to their new environment.